Reading inequities by the economic status of Texas grade 3 english language learners: A Texas, multiyear analysis - Gideon D Schleeter; John R. Slate; George W Moore; Frederick C Lunenburg (Journal of Education and Learning (EduLearn), 2020)
Analyzed in this investigation were the current Texas state-mandated assessments in reading and the extent to which test scores differed among English Language Learners who were Not Poor (i.e., did not qualify for the reduced or free lunch program), English Language Learners who were Moderately Poor (i.e., qualified for the reduced lunch program), and English Language Learners who were Extremely Poor (i.e., qualified for the free lunch program). In all cases, reading achievement was lowest for English Language Learners who were Very Poor, followed by English Language Learners who were Moderately Poor. English Language Learners who were Not Poor had the highest reading performance in all four school years. Implications for policy and practice, as well as recommendations for future research, are provided.